2016
DOI: 10.1155/2016/7684915
|View full text |Cite
|
Sign up to set email alerts
|

Current Role of Minimally Invasive Radical Cholecystectomy for Gallbladder Cancer

Abstract: Background. For Tis and T1a gallbladder cancer (GbC), laparoscopic cholecystectomy can provide similar survival outcomes compared to open cholecystectomy. However, for patients affected by resectable T1b or more advanced GbC, open approach radical cholecystectomy (RC), consisting in gallbladder liver bed resection or segment 4b-5 bisegmentectomy, with locoregional lymphadenectomy, is considered the gold standard while minimally invasive RC (MiRC) is skeptically considered. Aim. To analyze current literature on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…One concern is that laparoscopic access has been associated with a reduced lymph node yield. Open or laparoscopic access for resection appears to have no effect on outcome in early gallbladder cancers, whereas data on the minimally invasive approach in more advanced cancers (T2 or above) are based on small series and not established as a standard approach.…”
Section: Resultsmentioning
confidence: 99%
“…One concern is that laparoscopic access has been associated with a reduced lymph node yield. Open or laparoscopic access for resection appears to have no effect on outcome in early gallbladder cancers, whereas data on the minimally invasive approach in more advanced cancers (T2 or above) are based on small series and not established as a standard approach.…”
Section: Resultsmentioning
confidence: 99%
“…The most important risk factor is gallstones. The majority of GBCs are adenocarcinomas, followed by squamous cell, adenosquamous, and undifferentiated carcinomas [7].…”
Section: Hesham Abdeldayemmentioning
confidence: 99%
“…Outcomes following radical cholecystectomy with the minimally invasive approach are rarely reported . Two systematic reviews for the minimally invasive approach concluded that it cannot be considered as a dogmatic contraindication for GBC …”
Section: Introductionmentioning
confidence: 99%
“…11,12 Two systematic reviews for the minimally invasive approach concluded that it cannot be considered as a dogmatic contraindication for GBC. 13,14 Robotic surgery is evolving and it offers many technical advantages over laparoscopy. Since its inception, many technical modifications have been added to the da Vinci robotic surgical system (dVSS) benefitting the surgeon and improving patient outcomes.…”
Section: Introductionmentioning
confidence: 99%